The Effect of E-Service Quality and E-Perceived Value on E-Customer Loyalty with E-Convenience as a Mediating Variable - Gaotami, Elsa; Suryadi, Nanang; Hapsari, Raditha Dwi Vata (Journal of Social Research, 2023)
At this time the digital pharmacy industry is experiencing very rapid development, this can be seen from the increase in online pharmacy applications. Kimia Farma Mobile is one of the online pharmacy applications that is widely discussed in various pharmaceutical industries, besides that Kimia Farma Mobile was able to reach more than 900,000 users with a 4-star rating and also occupied the third position in the list of health applications in Indonesia in July 2022. This study aims to examine the effect of e-service quality and e-perceived value on e-customer loyalty with e-convenience as a mediating variable. This study uses quantitative research methods. Respondents in this study were Kimia Farma Mobile customers who had made transactions more than once. This study obtained 201 samples distributed via Whatsapp messages to customers. The data in this study were analyzed using SEM-PLS through the SmartPLS 3 program. The results of this study indicate that all hypotheses are accepted and significant, but e-service quality is not significant to e-customer loyalty.